Scarcity and Live Commerce Effects on Impulse Buying: Competitive Arousal in Kupang E-Commerce - Goetha, Selfiana; Niha, Simon Sia; Fallo, Apryanus (Universitas Pendidikan Nasional, 2024)
The objective of this study is to investigate the impact of scarcity messages, live commerce, and competitive arousal on impulse buying behavior. Unlike previous research that focused on consumer attitudes in traditional retail environments, this study explores the role of e-commerce applications in shaping consumer spending patterns under conditions of limited product availability and time constraints. Furthermore, it examines consumer interactions with sellers during live commerce sessions. This research employs a quantitative methodology, specifically utilizing hypothesis testing. The target population comprises residents of Kupang City who have engaged in purchases through e-commerce applications that feature live commerce sessions with restrictions on product availability and time (commonly referred to as flash sales). The sample size for this study consists of 450 respondents, selected through purposive sampling techniques. Data collection methods include both primary and secondary sources. Primary data is gathered through the distribution of questionnaires via Google Forms, while secondary data is obtained through literature reviews of relevant books and research studies. Additionally, observational data is collected from e-commerce platforms that conduct sales events. The data analysis is conducted using quantitative techniques, specifically employing the SEM-PLS analysis tool. The findings indicate that both scarcity messages and live commerce significantly influence impulse buying through competitive arousal; however, the effect of each variable is relatively modest. These results offer valuable insights for e-commerce messages and live streaming sessions on consumer impulsive behavior, businesses can develop more effective marketing strategies, such as leveraging flash sales or highlighting limitations in product availability and time.